Korelasi Konsentrasi Particulate Matter (PM10) di Udara dan Kandungan Timbal (Pb) dalam Rambut Petugas SPBU di Kota Pekanbaru - Vivi Roza; Mirna Ilza; Sofia Anita (Dinamika Lingkungan Indonesia, 2015)
This research describes the concentration of PM10 in the air and the Pb content inthe Gas Station Attendants’ hair in Pekanbaru. It was conducted in March – June 2014 byusing Case Control Survey Method and Statistical Analysis which are ANOVA Test andIndependent Sample t-Test in order to find out the difference of the Pb content in gas stationattendants’ hair of Pekanbaru City that is based on age, sex, location, group (case-control)and term of service and also to test the correlation between PM10 concentration and leadcontent (Pb) with a simple regression correlation analysis. The result reveals that there is nodifference in Pb content in the gas station attendants’ hair in Pekanbaru City based on age,sex, term of service and the group (case-control) (p>0,05). However, there are differences inthe Pb content in the gas station attendants’ hair based on the locations (p<0,05). PM10concentration and Pb content in the gas station attendants’ hair resulted an equation Y=0,151 + 0,001x. While R2=0,110 as a determinant coefficient showed a weak positiverelationship between the concentration of PM10 and Pb content in the gas station attendants’hair of Pekanbaru City.